A laugh a minute a laugh out loud collection of our funniest jokes, quotes, stories and cartoons (Reader's Digest (Australia) Pty Limited, 2008)
A laugh-out-loud collection of our funniest jokes, quotes, stories and cartoons If you're looking for a bit of laughter in your day, here is a collection of jokes, one-liners and other light-hearted glimpses of life that will prove the perfect pick-me-up. This bundle of laughs includes words of wisdom, provocative opinions and humorous anecdotes and cartoons drawn from the pages of Reader's Digest magazine as well as comedy scripts, TV shows and entertaining books and newspapers from around the world. Divided into topics such as Law and Disorder, What's Up, Doc? and Ageing Gracelessly, this compendium is an instant antidote to stress and anxiety.